Neurocysticercosis, Meningioma, and Silent Corticotroph Pituitary Adenoma in a 61-Year-Old Woman. (30th December 2012) - Ramirez, Maria del Pilar; Restrepo, Juan E.; Syro, Luis V.; Rotondo, Fabio; Londoño, Francisco J.; Penagos, Luis C.; Uribe, Humberto; Horvath, Eva; Kovacs, Kalman
Abstract : We report here the case of a 61-year-old woman who presented with hydrocephalus and cystic and solid lesions in sella turcica, suprasellar areas, and third ventricle. After ventriculoperitoneal shunt she developed cognitive changes and the cystic lesions enlarged. Magnetic resonance imaging (MRI) demonstrated multiple cysts and a solid lesion in the sella and around the anterior clinoid process. With diagnosis of neurocysticercosis she underwent craniotomy. Pathologic examination documented two different lesions: viable and dead cysticerci with inflaming infiltration and a left anterior clinoidal meningioma. At the second surgery, six weeks later via transnasal transsphenoidal approach a silent corticotroph pituitary adenoma was removed which was studied by histology, immunohistochemistry, and electron microscopy. To our knowledge, the occurrence of these three different lesions in the sellar area was not described before.